Lectures on probability and second order random fields - Bricio Hernández, Diego (Series on advances in mathematics for applied sciences, 1995)
This book of lecture notes contains theoretical background material required for computer generation of random fields, which is of interest in various fields of applied mathematics. The necessary probabilistic background suitable for applied work in engineering as well as signal and image processing is also covered. The book is a valuable guide for higher level engineering students